2014
DOI: 10.1016/j.homp.2013.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of effects of homeopathically potentised gibberellic acid on the growth of Lemna gibba L. in a randomised and blinded bioassay

Abstract: Gibbosity seems to be a necessary condition for reactivity of L. gibba to potentised GA3. Further still unknown conditions seem to govern effect direction and the pattern of active and inactive potency levels. When designing new reproducibility studies, the physiological state of the test organism must be considered. Variability might be an interesting parameter to investigate effects of homeopathic remedies in basic research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 44 publications
0
39
1
Order By: Relevance
“…Increased homeopathic treatment potentization procedure standardization is necessary for realistic attempts at reproducibility trials [46]. If consistently prepared remedies are available, corroborating in vivo breast cancer trials for the PBHRF standalone ultramolecular glioma treatment protocol, Ruta graveolens 6c and Calcerea phosphorica 3X.…”
Section: Future Researchmentioning
confidence: 94%
“…Increased homeopathic treatment potentization procedure standardization is necessary for realistic attempts at reproducibility trials [46]. If consistently prepared remedies are available, corroborating in vivo breast cancer trials for the PBHRF standalone ultramolecular glioma treatment protocol, Ruta graveolens 6c and Calcerea phosphorica 3X.…”
Section: Future Researchmentioning
confidence: 94%
“…9,15 In a former study with the Lemna bioassay, the growth state gibbosity was identified as a necessary factor for the responsiveness of L. gibba to a treatment with potencies of gibberellic acid. 17 In the present investigation with A. nitricum potencies, we did not predefine gibbosity as a possibly critical parameter, because its relevance was unknown during the planning and the experimental phase of the current study. Correspondingly, a possible influence of gibbosity on the responsiveness of L. gibba to the homeopathic treatment had to be assessed a posteriori using the growth-state protocols.…”
Section: Stability Of the Test System And Reproducibilitymentioning
confidence: 99%
“…This study was carried out to investigate the intralaboratory reproducibility of homeopathic basic research using the L. gibba bioassay. After investigating reproducibility of the effects of gibberellic acid potencies, 11,12,17 we were interested in the reproducibility of the effects of potentized A. nitricum, which Scherr et al had observed in their study published in 2009. 11,12 Using an ANOVA model, Scherr et al found a significant interaction between the two independent factors (1) ExpNr and (2) treatment with potencies of A. nitricum (14xe30x) in a series of six independent experiments.…”
Section: Stability Of the Test System And Reproducibilitymentioning
confidence: 99%
See 2 more Smart Citations